RELATIONSHIP OF INSTRUCTIONAL LEADERSHIP, ORGANIZATIONAL CLIMATE AND TEACHER’S COMMITMENT TO JOB SATISFACTION - Harahap, Maya Elizah; Suriansyah, Ahmad; Suhaimi (Journal of K6, Education and Management, 2019)
Teachers are the most important and dominant factor in education because they are educational servants who have a direct relationship with the students and also members of the school organization. Thus, the school principal`s role, conducive school environment, and teacher commitment should be maintained so that the job satisfaction of the teacher is fulfilled. This study aims to analyze the role of a principal, concerning leadership style, the provision of a conducive school environment, and ensuring teachers? commitment, to attain learning satisfaction in public elementary schools. This research was conducted in Tapin Utara District, with a sample of Ninety elementary school teachers selected at random. The analytical method used is the analysis method using the IBM SPSS 20. the results show that there is a direct and indirect relationship between instructional leadership, organizational climate, teacher commitment, and job satisfaction. the principal's leadership is the basis for the job satisfaction achievement for both teachers and staff in the organization, directly and through the organizational climate created and the commitment of each teacher.